Content analysis of food and beverage marketing in global esports: sponsorships of the premier events, leagues, teams and players - Robin Ireland; John William Long; Sara Jordan Maksi; Francisco Javier López Frías; Travis D Masterson (BMJ Publishing Group, 2024)
Background Food marketing has been implicated as a driving force of the obesity epidemic. Electronic sports, or 'esports', garners billions of viewership hours and is a consolidation of two major marketing outlets, online social media and sporting events, making it a focal point for food marketers and policy-makers.Methods The top 10 esports events and leagues were identified using data scraped between 1 January 2021 and 15 December 2021. The 10 teams within each league (90 total teams) and up to 10 players from each team (451 total players) were identified. Of the top 10 events and leagues, 6 events and 2 leagues were held or located outside the USA, reflecting the global popularity of esports. Food and beverage brands associated with each event, league, team or player were systematically identified and extracted via official websites and social media accounts. The number of sponsorships was totalled for each brand. Brands were then categorised based on product type into the following categories: energy drinks, sugar-sweetened beverages, alcohol, candy/snacks, restaurants, food delivery and stores, and supplements. The total number of brand sponsorships was then calculated for each product category.Results 90 unique food and beverage brands were identified. Across all brands, a total of 497 food brand sponsorships were identified. For product categories, energy drink brands had the most sponsorships (181 sponsorships, 36.4%), followed by restaurants (86 sponsorships, 17.3%) and candy/snacks (64 sponsorships, 12.8%). The individual brand with the most sponsorships was Monster Energy (47 sponsorships, 9.4%), followed by Jack Links (44 sponsorships, 8.8%) and Red Bull (42 sponsorships, 8.4%).Conclusion Despite its nascent character, the esports industry is already heavily saturated by food and beverage marketing. There is a need to consider policies to appropriately regulate food and beverage marketing within esports communities to safeguard the health of viewers.